2016
DOI: 10.24914/jeb.v17i1.240
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Kompetensi Terhadap Kinerja Pegawai Administrasi Perkantoran

Abstract: Keywords: Competency, Performance PENDAHULUANOrganisasi akan berkembang dan mampu bertahan dalam lingkungan persaingan yang kompetitif apabila didukung oleh pegawai-pegawai yang berkompeten di bidangnya. Pegawai merupakan aset organisasi yang vital karena memberi kontribusi besar sebagai penggerak roda organisasi dan aktor yang menjalankan tujuan organisasi. Dalam pelayanan administrasi perkantoran, pegawai

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 2 publications
4
18
0
25
Order By: Relevance
“…The results of this study also support the previous research conducted by Rizal et al (2013) using the SEM test, that competencies is the main factor affecting performance (path coefficient 0.81), with attachment reinforcement factors (path coefficient 0.78) and supporting factors of motivation (0.66) and job satisfaction (path coefficient 0.65). Research conducted by Kartika and Sugiarto (2014), shows that the competencies of office administration employees has a significant effect on performance. Research conducted by Rokhayati (2017) also found that soft skills as part of competencies proved to have a positive and significant effect on employee performance at PT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also support the previous research conducted by Rizal et al (2013) using the SEM test, that competencies is the main factor affecting performance (path coefficient 0.81), with attachment reinforcement factors (path coefficient 0.78) and supporting factors of motivation (0.66) and job satisfaction (path coefficient 0.65). Research conducted by Kartika and Sugiarto (2014), shows that the competencies of office administration employees has a significant effect on performance. Research conducted by Rokhayati (2017) also found that soft skills as part of competencies proved to have a positive and significant effect on employee performance at PT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the harmony of the quality culture of individual leaders and organizational actors will be formed. Based on previous and theoretical studies related to organizational behavior, it is known that many factors can determine a person's success in their field of work, such us organizational commitment (Geisler, Berthelsen, & Muhonen, 2019;Holsblat, 2014), professionalism (Jie, Mansor, & Kelana, 2020a, 2020b, and level of competence in the area they occupy (Kartika & Sugiarto, 2016;Supriyadi & Sarino, 2019).…”
Section: A University Quality Assurance Team Should Strive For Quality Of Work-lifementioning
confidence: 99%
“…Menurut (Kartika & Sugiarto, 2014) pengertian kompetensi dalam kenyataannya belum ada kesepakatan universal dan beberapa pakar memberikan pengertian yang cukup bervariasi.…”
Section: Kompetensiunclassified